Associations between seasonal variation and post-operative complications after total hip arthroplasty - Ng, Mitchell; Song, Simeng; George, Jaiben; Khlopas, Anton; Sodhi, Nipun; Ng, Kenneth; Sultan, Assem A.; Piuzzi, Nicolas S.; Mont, Michael A. (Annals of Translational Medicine, 2017)
Background: Total hip arthroplasty (THA) complication rates are low, but pose marked challenges during the post-operative care period. Therefore, it is important to determine which risk factors are associated with an increased rate of these complications. The purpose of this paper was to investigate the association between seasonal variations and the 30-day post-operative complication rates following THA. Specifically, we evaluated a large prospectively collected national database for: (I) overall complication rates; (II) seasonal variations in incidence; and (III) specific quarter (Q), if any, associations. Methods: This multi-center observational cohort study was conducted by analyzing 102,682 THA surgeries listed in the American College of Surgeon National Surgical Quality Improvement Program database (ACS-NSQIP) from January 1st, 2011 to December 31st, 2015. All surgeries were divided into 4 groups based on the quarter of the year in which the surgery was performed. We identified 20 complications listed in the ACS-NSQIP and calculated 30-day post-operative complication rates. Univariate analysis was performed to compare complication rates between different seasons. Multivariate analysis was performed to control for potential confounding variables. Results: The overall complication rate in this cohort was 1.09%. Upon tabulation of the different post-operative THA complication incidence rates sorted by quarters, 16 out of 20 outcomes had